NEGARA PANCASILA SEBAGAI DAR AL-‘AHDI WA AL-SYAHADAH MUHAMMADIYAH: RESPON TERHADAP ISLAMISME - Adlan Ryan Habibie (IAIN Manado, 2023)
Abstrack: This article aims to see how the decision of the Pancasila state as Dar al-‘Ahdi wa as-Shahadah was Muhammadiyah's response to the ideology of political Islam or Islamism. The approach used in this article is a qualitative approach using philosophical analysis. The primary Data of this study were taken from the manuscript of the state of Pancasila as Dar Al-‘Ahdi wa al-Shahadah published by the Central Board of Muhammadiyah. The results showed that the state of Pancasila as Dar Al - ' Ahdi wa Al-Shahadah decided by Muhammadiyah at the 47th Congress in 2015 in Makassar showed that the state of Pancasila is the result of national consensus and a proving ground to be a safe and peaceful country. For Muhammadiyah in the text of the Pancasila state decision as Dar al - ' Ahdi wa as-Shahadah, Pancasila as the basis of the state also contained Islamic and Indonesian values at the same time.Key Words: Pancasila State, Dar al-‘Ahdi wa as-Syahadah, Islamism.Abstrak: Artikel ini bertujuan untuk melihat gagasan Negara Pancasila sebagai Dar al-‘Ahdi wa as-Syahadah sebagai respon Muhammadiyah terhadap ideologi Islam politik atau Islamisme. Metode yang digunakan adalah kualitatif dengan kajian kepustakaan dengan pendekatan analisis tematik terhadap dokumen Keputusan Muhammadiyah tentang Negara Pancasila sebagai Dar al-‘Ahdi wa as-Syahadah. Hasil penelitian menunjukkan bahwa Negara Pancasila sebagai Dar Al-‘Ahdi wa Al-Syahadah yang digagas Muhammadiyah mengandung pengertian bahwa Negara Pancasila sudah merupakan rumusan final sebagai kesepakatan bersama di atas Negara Kesatuan Republik Indonesia. Lewat gagasan ini Muhammadiyah juga dengan tegas menolak ideologi islamisme yang bertujuan mengubah dasar negara.Kata kunci: Negara Pancasila sebagai Dar al-‘Ahdi wa as-Syahadah, Islamisme.